(untitled) (Revista Angelus Novus, 2024)
From the analysis of sources, contrasted with reflections by Jason Stanley and Federico Finchelstein, we explored the explanatory potential of the concept of fascism to understand the rhetorical acts of Bolsonaro during the 2018 elections and the beginning of his term. After a introduction and contextualization of this case, based on the program registered by the PSL candidate at TSE, we present the points of the Bolsonarist narrative. Following, we present the ideal type developed by Stanley and Finchelstein to analyze the historical sources. In conclusion, to reinforce the interpretations and to point out other readings, complementary ones from other authors are introduced. Although we emphasize the convergences, we do not ignore the divergences, which legitimize the extensive discussion about the best definition of Bolsonarism and the like, putting in check the pertinence of the use of the concept of fascism.